Bacterial Isolates and Antimicrobial Susceptibility Profiles in Wound Swabs from Central Polokwane NHLS, in Limpopo Province, South Africa (African Journal of Biomedical Research, 2019)
Bacteria are a major cause of wound infections with associated emergence of drug resistance to commonly used antimicrobials. This situation necessitates proper identification of the wound microbiota and their respective antimicrobial susceptibility profiles. A total of 88 wound swab specimens were collected and cultured by standard microbiological methods. The antibiotic susceptibility test of the bacterial isolates was performed by Kirby-Bauer disk diffusion method. Seven different species of bacteria were isolated. The most common organism isolated was Staphylococcus aureus (29%) followed by Staphylococcus epidermidis (15%), lactose fermenting coliforms (15%), Pseudomonas species (11%), Klebsiella species (7%) as well as Eschericia coli (3%) and Streptococcus group D (3%). Only 1% of Staphylococcus saprophyticus was isolated. All the positive samples were monomicrobial. Fourteen (14) samples showed no growth. The majority of the isolates were resistant to almost all the antimicrobials tested. Streptococcus group D was sensitive to mupirocin and oxacillin while Eschericia coli exhibited sensitivity for colistin sulphate and gentamicin. A high rate of multiple antibiotic resistant isolates was observed in both gram-positive and -negative bacteria. The results are presumptive of the likelihood of a changing resistant profile among the specimen tested. That might be attributable to various factors and warrants further investigation.
Keywords: Wound infections; bacteriology; susceptibility patterns; multi-drug resistance